Study on seed oil productionin different diameter classes of wild pistachio (Pistachia atlantica Desf.)in Chaharmahal and Bakhtiari Province - Hasan Jahanbazy Goujani; Yaghoub Iranmanesh; Mahmoud Talebi (تحقیقات جنگل و صنوبر ایران, 2015)
Wild pistachio (Pistachia atlantica Desf.) is one of the economically important woody species in Zagros region of Iran. Because of its economic importance, this species has an essential role in protecting soil and water resources. The possibility of seed oil extraction adds to the economic advantages of Pistacia atlantica. This study in Lordegan forests aims to determine the amount of seed production, oil percentage and chemical properties (e.g. fatty acid) to quantify the economic value of wild pistachio. Initially, 3 trees were selected in each diameter class ranging from 10 to 50 cm. The seeds of all trees were collected to measure the amount of seed and oil percentage in each diameter class. The Soxhlet analysis showed oil production of 27.16%, whereas rated 19.3% by using the mechanical analysis. Maximum oil production as measured by Soxhlet method was shown to be 32.1% for the diameter class of 45 cm. In addition, minimum production rate of 23.48% was recorded for the diameter class of 40 cm. The maximum seed oil of 24.8% was recorded by using the under pressure method in diameter class of 50 cm, while the same method resulted in the minimum oil amount of 16.85% in diameter class of 40 cm. The analysis of the samples revealed 13 fatty acids, including 7 unsaturated (Oleic, Iso-sic-oleic, Linoleic, Linolenic, Palmitoleic, Gadoleic, Behenic) and four saturated (Palmitic, Stearic, Miristic, Arachidonic) in oil extractedform Pistacia atlantica seeds.